Supplementation of grazing beef cattle with narasin - Gobato, Luiz Guilherme Mezzena; Polizel, Daniel Montanher; Ferraz Júnior, Marcos Vinícius de Castro; Miszura, Alexandre Arantes; Barroso, José Paulo Roman; Martins, André Storti; Gonçalves, José Renato Silva; Ferreira, Evandro Maia; Pires, Alexandre Vaz (Pesquisa Agropecuaria Brasileira, 2020)
The objective of this work was to evaluate the effect of narasin inclusion in mineral and protein supplements on the performance and supplement intake of grazing beef yearlings. One hundred and fifty Nellore yearlings with 17.0±0.06 months of age and 219.7±1.62 kg initial body weight (BW) were allocated into 30 experimental units (EUs), with five animals each. The EUs were assigned to 16 paddocks, which were continuously stocked for 28 days, followed by 28 days of rest. A randomized complete block design was used. The experiment lasted 140 days, divided into five periods of 28 days each. The assessed treatments were: control mineral supplement (CON); CON + 1,800 (N1800) or 2,750 (N2750) mg narasin per kilogram of supplement; and protein mineral supplement (PROT) or PROT + 360 mg narasin per kilogram of supplement (PROT 360). The inclusion of narasin in the mineral supplement increased average daily gain (ADG) in the first period and decreased supplement intake in the first, second, and third periods, when compared with the CON treatment. The ADG and supplement intake were similar between the N1800 and N2750 treatments. Narasin has a positive effect on ADG up to 28 days of supplementation and controls mineral supplement intake, without compromising this gain.
Keywords: Bos indicus; ionophore; nutrition